Drying tea in a kilburn vibro fluid bed dryer (Journal of the Bangladesh Agricultural University, 2014)
The fluidized bed drying principles for drying of tea in Bangladesh is thoroughly studied. The experiments were conducted to determine the drying curve, drying time, drying constant and dynamic equilibrium moisture contents of tea at the Bangladesh Tea Research Institute. Drying of tea in a fluidized bed dryer (Kilburn Vibro Fluid Bed Dryer) takes only 20 min for drying from an initial moisture content of 69.1% to a final moisture content of 2.8%. Temperatures of drying air were recorded to be 130°C at the inlet and 90°C at the outlet. The drying constant was found to be 31.05 h-1 and the dynamic equilibrium moisture contents were in the range of 18.3 to 2.0%. Finally the principle of fluidized bed drying was compared with the principle of conventional endless chain pressure type drying. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18227 J. Bangladesh Agril. Univ. 11(1): 153-158, 2013